2020
DOI: 10.1111/obr.13004
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into adiponectin action in breast cancer: Evidence of its mechanistic effects mediated by ERα expression

Abstract: Summary This review describes the multifaceted effects of adiponectin on breast cancer cell signalling, tumour metabolism, and microenvironment. It is largely documented that low adiponectin levels are associated with an increased risk of breast cancer. However, it needs to be still clarified what are the extents of the decrease of local/intra‐tumoural adiponectin concentrations, which promote breast tumour malignancy. Most of the anti‐proliferative and pro‐apoptotic effects induced by adiponectin have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 175 publications
(265 reference statements)
0
24
0
Order By: Relevance
“…Adiponectin activates the cytokine signaling responsible for the inactivation of leptin-induced AKT and STAT3 activation as well as Wnt signaling [109,110]. It is suggested that low levels of adiponectin are associated with high grade tumors, which might be due to an interference in its signaling via AMPK, which has an antiproliferative effect [111]. Studies also suggest that considering leptin or adiponectin concentration individually in plasma is not correct, the true measurement is the ratio of the two, as different concentrations of each can be found in BC cell lines [112][113][114][115].…”
Section: Adiponectinmentioning
confidence: 99%
“…Adiponectin activates the cytokine signaling responsible for the inactivation of leptin-induced AKT and STAT3 activation as well as Wnt signaling [109,110]. It is suggested that low levels of adiponectin are associated with high grade tumors, which might be due to an interference in its signaling via AMPK, which has an antiproliferative effect [111]. Studies also suggest that considering leptin or adiponectin concentration individually in plasma is not correct, the true measurement is the ratio of the two, as different concentrations of each can be found in BC cell lines [112][113][114][115].…”
Section: Adiponectinmentioning
confidence: 99%
“…In ERα-positive breast cancer cells, LKB1 binds to ERα and in doing so makes its cytosolic pool not adequate to activate AMPK signaling, thus maintaining mTOR signaling and sustaining cell growth ( Ando et al, 2020 ). To investigate the biological effect of ER-α on tumorigenesis in ER-α-positive EC, mRNA and protein levels of genes in the LKB1/AMPK/mTOR pathway were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Adiponectin has also been linked with breast cancer progression but has shown mostly anti-tumorigenic effects [ 170 , 171 , 172 , 173 , 174 ]. The effect on breast cancer progression seems to depend on ER status [ 170 ]. With increasing BMI, the levels of adiponectin in serum decreases [ 175 ].…”
Section: Breast Cancer Progression and Local Obesity-associated Biomarkersmentioning
confidence: 99%